PERAN MODERASI KONVERGENSI IFRS DALAM HUBUNGAN ANTARA AGRESIVITAS PELAPORAN KEUANGAN DAN RETURN - Saring Suhendro (Jurnal Akuntansi dan Keuangan (JAK), 2019)
The purpose of this study is to examine the effect of accrual information quality and the role of IFRS convergence on earnings informativeness measured by ERC in relation to stock price movements occurring in Indonesia. Using manufacturing companies that went public and were listed on the Indonesia Stock Exchange in 2004-2013. The use of sample companies in 2004-2007 was before the IFRS convergence and in 2008-2013 after the IFRS convergence. The results showed that earnings response coefficient on earnings information decreased due to reported earnings containing high discretionary accruals. While investor perceptions (ERC) increased after the IFRS convergence.